Atlas of Woody Plant Stems Evolution, Structure, and Environmental Modifications - Schweingruber, Fritz Hans; Börner, Annett; Schulze, Ernst-Detlef (Springer Berlin Heidelberg : Imprint: Springer, 2008)
he "Atlas of Woody Plant Stems" is a com- Naturally, it was impossible to cover completely the Tprehensively illustrated book with short, in- enormous variability of plant life forms. We have formative texts. We chose this layout because plant tried, however, to illustrate the main principles and anatomy and morphology can only be conveyed by features. Many decades of collection and prepa- detailed pictures. In addition, a vivid presentation tion provided the basis for this book. should attract a broader public, not only the s- cialist. We hope that the combination of anatomy Fritz Schweingruber would like to thank the Swiss and morphology will create interest and curiosity. Federal Research Institute WSL, that offered him Amateurs will enjoy the wide range of pictures; hospitality after his retirement. The authors thank all interested readers will be caught by particular chap- the students and colleagues that have, for decades, ters; specialists will delve into aspects and photo- collected and prepared samples, and who helped graphs that may have never been presented before; with the English translations. Thanks to John Kirby teachers may use the pictures for illustrations in who made the fnal English editing. classes with students.